Security of tenure for retirement village residents in WA - Does the law walk the walk or just talk the talk? - Levine, Pnina (University of Western Australia Law Review, 2015)
Until recently, the legislation governing retirement villages in Western Australia had not been altered significantly. In 2014, significant amendments were made. The legislation has also recently been judicially considered in the Supreme Court case of Retirement Care Australia (Hollywood) Pty Ltd v Commissioner for Consumer Protection [2013] WASC 219, and the case may have serious consequences for the retirement village industry. This paper examines the effect of the current legislative framework regulating retirement villages on residents' security of tenure, both in terms of their legal right and their practical option to remain in a village. It also discusses some unresolved issues and possible unintended consequences that may arise out of the legislation. The obvious point is that the regulation of the retirement village industry, including any reforms made to it, will only be as effective as the extent to which there are sufficient mechanisms to enforce compliance by operators and adequate resources have to be allocated to regulatory authorities for any amendments to achieve their purpose.